Bipolar Valued Multi Fuzzy Normal Subnear-Ring of a Near-Ring - Muthukumaran, S.; Anandh, B. (Communications in Mathematics and Applications, 2023)
In this paper, bipolar valued multi fuzzy normal subnear-ring of a near-ring is introduced and some theorems are stated and proved.